Niilism and gnosticism: from world’s denial to earth’s faithfulness in Nietzsche’s Zaratustra - Roberto de Oliveira, Jelson (2022)
Starting from the interpretation of nihilism as a denial of life, this text intends to demonstrate how Zarathustra's exhortation of "fidelity to the earth" can be understood as a form of confrontation with nihilism in the work of F. Nietzsche. To this end, we will start from an intratextual analysis of the relationship between nihilism and Gnosticism in the work of the German philosopher in order to demonstrate how the historical founding character of Zoroastrianism is presented through a dualistic moral whose Gnostic premises lead to nihilism as a negation of the world and, from there, how the literary character created by Nietzsche is effective as a counterpoint to this perspective, through a new link between human beings and the world. In this way, we intend to demonstrate that, with his exhortation, Nietzsche's Zarathustra became the one who self-suppresses the morality founded by his historical namesake and led to the transvaluation of values through the creation of new virtues.